2000
DOI: 10.1007/s002280000161
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of etodolac and ibuprofen on renal haemodynamics, tubular function, renin, vasopressin and urinary excretion of albumin and α-glutathione- S -transferase in healthy subjects: a placebo-controlled cross-over study

Abstract: In conclusion, a 14-day administration of etodolac or ibuprofen in therapeutic doses did not affect the renal haemodynamics, the net excretion of electrolytes or the urinary excretion of albumin in healthy subjects. However, ibuprofen, in contrast to etodolac, caused a reduction in PRC, suggesting that COX-1 is involved in basal renin release in humans. Furthermore, ibuprofen decreased lithium excretion suggesting that COX-1 is involved in the re-absorption of sodium and/or water in the proximal tubuli. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Furthermore, potassium excretion was reduced after administration of naproxen and celecoxib at day 1 but even more clearly at day 7 (F40 Ìmol K + /min 2 and 3 h after dosing) [63]. When taking these results [63] into account it was no surprise that in healthy volunteers on a high sodium diet no effect of treatment for 14 days with either etodolac or ibuprofen on sodium and potassium excretion was found (table 1) [64].…”
Section: Human Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, potassium excretion was reduced after administration of naproxen and celecoxib at day 1 but even more clearly at day 7 (F40 Ìmol K + /min 2 and 3 h after dosing) [63]. When taking these results [63] into account it was no surprise that in healthy volunteers on a high sodium diet no effect of treatment for 14 days with either etodolac or ibuprofen on sodium and potassium excretion was found (table 1) [64].…”
Section: Human Studiesmentioning
confidence: 85%
“…Due to the experimental protocol used, the volunteers had to receive water loading thereby probably masking potential differences [63]. Similarly, Svendsen et al [64] in their study with healthy volunteers on an unrestricted (high) sodium diet found no significant effect of treatment with the preferential COX-2 inhibitor etodolac but a 32% reduction of PRC (plasma renin concentration) after ibuprofen (water load of 600 ml before taking a PRC sample).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nonsteroidal anti-in fl ammatory agents (NSAIDs) also have important effects on lithium clearance and can increase circulating concentrations of lithium to potentially toxic levels. This interaction is well established for ibuprofen, is much less likely with some COX-2 inhibitors, and may be limited also with acetaminophen and naproxen [ 214,320 ] . Another class of agents with potent ability to increase circulating concentrations of lithium are the angiotensinconverting enzyme (ACE) inhibitor antihypertensive drugs such as lisinopril (Zestril ® [ 114,236 ] ).…”
Section: Lithiummentioning
confidence: 91%
“…Urinary glutathione-S-transferases (GSTs) have been used to detect tubular injury. [7,11] GSTs are cytosolic enzymes that have many isomers. GST and GST are the main isomers in the kidney.…”
Section: Introductionmentioning
confidence: 99%